SISTEM PENYELENGGARAAN MAKANAN, TINGKAT KONSUMSI DAN STATUS ANEMIA DI ASRAMA PROGRAM STUDI KEBIDANAN SOETOMO POLTEKKES KEMENKES SURABAYA - Ani Intiyati; Eny Sayuningsih; Inne Soesanti (Poltekkes Kemenkes Surabaya, 2016)
Soetomo midwifery student dormitory is one of the 12 polytechnic hostel in Surabaya having food management administration system for students. At the hostel, diet comes from studentrequests that are tailored to the existing budget. The purpose of this study is knowing influence theorganization of food management system to the level of consumption and the incidence of anemiain the dorm Midwifery Soetomo. Type of the research is a descriptive analytic study with cross sectional design. Samplesnumbered 44 by simple random sampling. The collection of data by interview and observation.Analysis of the data is tested with Spearman's rho. The conclusion of this study is the implementation of the food system in the dorm obstetricsis not all conform to the standard system for the implementation of institutional food energyconsumption levels are normal and there is no severe deficit and slightly anemic. At the level ofprotein intake, many normal and mild deficits. To the level of iron consumption, the deficit morenormal, but many are not anemic, and the level of vitamin C is normal, 6 people (13.6%) sufferedfrom anemia and 38 persons (86.4%) not anemia. From the test results Rho Spearmant, there isno influence of the level of consumption of energy, protein, foods containing Fe and vitamin C onthe incidence of anemia. Keywords: the level of consumption of energy, protein, foods containing Fe and vitamin C, Anemia